Digital literacy and its relationship with employee performance in the 4IR / Mohd Khalid Mohd Abas, Ros Aizan Yahaya and Mohd She Fee Din - Mohd Abas, Mohd Khalid; Yahaya, Ros Aizan; Din, Mohd She Fee (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2019)
Work in the oil and gas industry today in general has rapidly grow alongside with the advancement of digital technology. However, many employees are facing issues of coping and keeping up with the technological knowledge in completing their work. This study investigates the relationship between digital literacy and employee performance in the oil and gas industry in Malaysia. The technological, organizational and environmental (TOE) context was applied to measure the influencing factors. Stratified sampling method was used to attain information from two divisions of the organization. Data was analyzed using correlational analysis and multiple regression methods. Outcome of this study suggests that there is a positive relationship between digital literacy in technological context, organizational context, environmental context and employee performance. It is suggested that a good foundation in the technological and organizational infrastructure is needed to increase digital literacy among employees. For future research, readiness in embracing digital literacy should be made at the managerial level in this industry.